1970
DOI: 10.1063/1.1674033
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Properties of a Rigid-Sphere Fluid

Abstract: The excess thermodynamic properties for a rigid-sphere fluid have been calculated with an accurate equation of state. Values of (PV / NkT), and (H − H°) / RT, (S − S°) / R, (G − G°) / RT, and (f / P) are reported for a wide range of fluid density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 218 publications
(104 citation statements)
references
References 9 publications
4
95
0
Order By: Relevance
“…The fluidicity problems, including the singularity in entropy at zero frequency due to diffusion and the anharmonicities at lowfrequency regime, are resolved by decomposing the liquid S(υ) into a solid S s (υ) and a gas S g (υ) component, and treating each component with appropriate statistics. Lin et al have shown 40 The details of how to decompose S(υ) into S s (υ) and S g (υ) can be found in ref 35. Also note that the entropic contribution from molecular rotations is assumed to be a constant value of 44.58 J/(mol K) (3.2 kcal/mol in terms of TS at 300 K) as previous studies have shown that the rotational entropy in solution can be well estimated from the value in the ideal gas condition.…”
Section: Change Of Water Translation and Rotation Dynamics Under Diffmentioning
confidence: 99%
“…The fluidicity problems, including the singularity in entropy at zero frequency due to diffusion and the anharmonicities at lowfrequency regime, are resolved by decomposing the liquid S(υ) into a solid S s (υ) and a gas S g (υ) component, and treating each component with appropriate statistics. Lin et al have shown 40 The details of how to decompose S(υ) into S s (υ) and S g (υ) can be found in ref 35. Also note that the entropic contribution from molecular rotations is assumed to be a constant value of 44.58 J/(mol K) (3.2 kcal/mol in terms of TS at 300 K) as previous studies have shown that the rotational entropy in solution can be well estimated from the value in the ideal gas condition.…”
Section: Change Of Water Translation and Rotation Dynamics Under Diffmentioning
confidence: 99%
“…where z is the compressibility, which can be obtained from the accurate Carnahan-Starling equation of state 9 for hard spheres z͑ y ͒ϭ 1ϩyϩy 2 Ϫy 3 ͑ 1Ϫy ͒ 3 ͑30͒…”
Section: ͑24͒mentioning
confidence: 99%
“…To approximate the excess free energy density f exc ͑n͑r͒͒ per unit volume of the reference system of density n, CarnahanStarling's formula 19 …”
Section: ͑13͒mentioning
confidence: 99%